A baseline study on mercury concentrations in the surface sediments of the Straits of Malacca collected during four sampling cruises conducted between 1998-200 - Yap, Chee Kong; Ismail, Ahmad; Tan, Soon Guan (Scientific Publishers, 2010)
Total elemental mercury (Hg) levels in the surface sediments along the Straits of Malacca were analysed by using a Hg Analyzer Model MA-1S. Based on four sampling cruises conducted between 1998- 2000, the Hg levels in more than 95% of the sampling sites were lower than 100 μg/kg dry weight while the Hg range was between 9.86-202 μg/kg dry weight with the northern part of the Strait recorded higher concentration of Hg when compared to central and southern parts. In comparison to other regional results and established sediment quality guidelines for Hg, Hg contamination in the Straits is not serious but regular monitoring of this hazardous element is necessary.